Genome-Wide Associations of Chlorophyll Fluorescence OJIP Transient Parameters Connected With Soil Drought Response in Barley - Rapacz, Marcin; Wójcik-Jagła, Magdalena; Fiust, Anna; Kalaji, Hazem M.; Kościelniak, Janusz (Frontiers in Plant Science, 2019)
One hundred and nine accessions of spring barley seedlings were phenotyped under soil drought conditions. Chlorophyll fluorescence induction (OJIP) parameters, leaf water content, relative turgidity, net assimilation rate (PN) and water use efficiency (WUE) of plants were measured. All the tested lines were genotyped by means of DArT sequencing (DArTseq) technology. For association mapping a 11,780 polymorphic DArTseq and 4,725 DArTseq SNP markers were used. Our results revealed dissimilar patterns of the relationships between OJIP-parameters under control and drought conditions. High level of correlation between parameters characterizing Photosystem’s II (PSII) energy trapping efficiency (Fv/Fm) and photochemical events downstream of PSII reaction center (e.g. Performance Index - PICSo) was observed only in the case of drought treated plants. Generally, OJIP parameters were correlated with leaf water content (less in control). This correlation was weaker with WUE, and absent with PN. Under drought stress, a 6252 genotype × phenotype associations, which passed false discovery rate (FDR) verification, were found between all the studied phenotypic characteristics (23, including 19 OJIP parameters) and 2721 markers. On the other hand, only 282 associations passed FDR test in the control. They comprised 22 phenotypic parameters and 205 markers. Probing for gene annotations of sequences was performed for markers associated with Fv/Fm for both drought and control, markers associated with studied traits in both control and drought, as well as for markers associated with both OJIP and other physiological parameters in drought. Our work allowed us to conclude that, drought treatment differentiates the studied lines through the revealing of relationships between water content and the damages to PSII reaction centers or different components of PSII energy transfer chain. Moreover, the former was not connected with net photosynthesis rate.